Pseudogapping, Parallelism, and the Scope of Focus. (5th July 2016) - Thoms, Gary
Abstract: In this paper I defend a particular analysis of pseudogapping in which the focused remnant is moved by leftward A′‐movement (Jayaseelan2002, Gengel2013 ). Noting the superficial similarity between pseudogapping and stripping, I show that pseudogapping is much more restricted than we would expect if it were just another version of stripping, failing to apply across clause boundaries and allowing a much narrower range of remnants. I provide an analysis of these restrictions in terms of Parallelism, arguing that the difference between pseudogapping and stripping is keyed to the different ways in which their correlates may take scope. The proposal accounts for the exceptional behavior of pseudogapping in comparatives, and it leads us to the conclusion that there exists a set of movement operations that occur only in the context of ellipsis.